Impact of a multimodal intervention to reduce bloodstream infections related to vascular catheters in non‐ICU wards: a multicentre study. (6th November 2012) - Freixas, N.; Bella, F.; Limón, E.; Pujol, M.; Almirante, B.; Gudiol, F.
<x xml:space="preserve">Abstract</x> Clin Microbiol Infect Abstract To determine the impact of a multimodal intervention designed to reduce the incidence of catheter‐related bloodstream infections (CRBSIs) outside the ICU, we conducted a prospective, quasi‐experimental, before‐after intervention study in 11 hospitals participating in the VINCat programme in Catalonia, Spain. The intervention consists of: (i) an evidence‐based bundle of practices relating to catheter insertion and maintenance; (ii) a training programme for healthcare workers; (iii) four point–prevalence surveys to track the status of the catheters; and (iv) feedback reports to the staff involved. The study included both central (CVC) and peripheral venous catheters (PVCs). Rates of CRBSI per 1000 patient‐days were prospectively measured in 2009 (pre‐intervention period) and 2010 (post‐intervention period). The analysis included 1 191 843 patient‐days in 2009 and 1 173 672 patient‐days in 2010. The overall incidence of CRBSI decreased from 0.19 to 0.15 (p 0.04) and the incidence of CRBSI associated with a CVC decreased from 0.14 to 0.10 (p 0.004) after the intervention. The incidence in PVCs remained unchanged. There was a statistically significant improvement in the adequate maintenance of both CVCs and PVCs. Among the CRBSIs originating in PVCs, 61.8% appeared more than 72 h every insertion. There was a lower infection rate in the hospitals with a higher adherence to the recommendation to replace PVCs after 72 h. Our findings suggest that the implementation of intervention programmes similar to ours could have a major impact on patient safety by reducing the incidence of CRBSIs, and that routine replacement of PVCs might additionally prevent a significant number of bloodstream infections.